A meta-analysis of risk factors for cage migration after lumbar fusion surgery - Yang Hou; Haoyang Shi; Hongyang Shi; Tianyi Zhao; Jiangang Shi; Guodong Shi (World Neurosurgery: X, 2023)
Objective: Cage migration is a rare complication after lumbar fusion surgery, and it is also the cause of lumbar revision surgery. Previous studies have reported that many influencing factors can increase the incidence of cage migration. However, there still remains controversial. The current study was conducted to investigate the risk factors influencing incidence of cage migration. Methods: A systematic database search of PubMed, Embase, Web of Science, Cochrane Library and Clinical Trials was performed for relevant articles published until July 2022. According to the inclusion and exclusion criteria, two evaluators independently conducted literature screening, data extraction and quality evaluation of the obtained literature. The Newcastle–Ottawa Scale (NOS) score was used for quality evaluation, and meta-analysis was performed by STATA 16.0 software. Results: A total of 2126 relevant articles were initially identified, and 7 articles were finally included in this study for data extraction and meta-analysis. The results of meta-analysis showed that the bony endplate injury, pear-shaped disc, and screw loosening are significantly correlated with cage migration. The OR values (95%CI) of the three factors were 7.170 (3.015, 17.051), 8.056 (4.050, 16.023), and 12.840 (3.570, 46.177) respectively. Conclusion: Bony endplate injury, pear-shaped disc, and screw loosening are the current risk factors for cage migration postoperatively.